2019
DOI: 10.1016/j.aop.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Landau levels in the presence of a cosmic string in rainbow gravity

Abstract: In this paper we analyze the energy levels of a charged scalar particle placed in the static cosmic string spacetime, under the action of a uniform magnetic field parallel to the string, in the context of the semi-classical approach of the rainbow gravity. Firstly, we focus on the non-relativistic regime by solving the corresponding Schrödinger equation, following by a complete relativistic treatment of the problem in which we considered the Klein-Gordon equation. In both cases we find exact expressions for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Moreover, we have observed that square the energies in (18) (i.e., E 2 ) resembles the Landau-type energies-squared with an irrational magnetic quantum number γ that indulges within the Aharonov-Bohm flux field effect. We may argue, therefore, that the additional compact dimension of the Kaluza-Klein theory offers quasi-Landau energy levels (e.g., [6,64,67]). Hereby, the behaviour of the energy levels E nr ,ℓ is found to follow two different trends of clustering and batching up for the curvature parameter α ≈ 0 and α ≫ 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we have observed that square the energies in (18) (i.e., E 2 ) resembles the Landau-type energies-squared with an irrational magnetic quantum number γ that indulges within the Aharonov-Bohm flux field effect. We may argue, therefore, that the additional compact dimension of the Kaluza-Klein theory offers quasi-Landau energy levels (e.g., [6,64,67]). Hereby, the behaviour of the energy levels E nr ,ℓ is found to follow two different trends of clustering and batching up for the curvature parameter α ≈ 0 and α ≫ 1.…”
Section: Discussionmentioning
confidence: 99%
“…where n r = 0, 1, 2, • • • is the radial quantum number (denotes number of nodes in the wave function) (c.f., e.g., [60,[64][65][66]). Hence, the KG-oscillator of ( 16) admits exact energy levels given by…”
Section: Kg-oscillator In Cosmic String Spacetime Within Kkt: Recycle...mentioning
confidence: 99%
See 1 more Smart Citation
“…where the exponential form of these functions is useful to explain observational data of gamma ray bursts at cosmological distances [26,27].…”
Section: Dispersion Relationsmentioning
confidence: 99%
“…In the scenario of gravity's rainbow, the Landau levels [33] and the Dirac oscillator [34] in the presence of a cosmic string have been studied. In the present paper, we will consider scalar particles in a cosmic string space-time in the context of gravity's rainbow and obtain the solutions of the KG equation, with both minimum (Coulomb-like) and non-minimum coupling (KG oscillator) in two scenarios of the gravity's rainbow, and analyze their consequences.…”
Section: Introductionmentioning
confidence: 99%